Understanding Company Values Through Good Corporate Governance Mediation - Damanik, Florencius Bona Marihot; Widjajanti, Kesi; Lestari, Dian Indriana Tri (Quantitative Economics and Management Studies, 2024)
The aim of this research is to determine the influence of investment policies, policies funding and dividend policy on company value and the role of good corporate governance (GCG) in mediating the influence of investment policies and policies funding and dividend policy on company value. This research is quantitative research using secondary data manufacturin companies listed on the Indonesia Stock Exchange (BEI) within a year period 2018 to 2022. Sample selection used the purposive sampling method thus obtaining 37 companies that met the criteria from a total population of 239 manufacturing company. This research was tested using the Structural Equation analysis method Modeling (SEM) with the Smart PLS 3.0 program. The research results show that GCG is not successful in mediating the influence of policy investment, funding policy and dividend policy on company value, though investment policy has a positive and significant effect on GCG, funding policy has a positive and significant effect on GCG, investment policy has a positive and significant effect significant to company value and dividend policy has a negative and significant effect on company value. Then, dividend policy has a negative or negative effect significant to GCG. GCG has a positive and insignificant effect on value company. Funding policy has a positive and insignificant effect on value company.